Enteric Fever as an Antecedent to Development of Miller-Fisher Syndrome and Possible Role of COVID-19 Vaccination - Saleem, Tayyaba Binte; Ibrahim, Muhammad; Fazal, Faizan; Rehman, Mohammad Ebad Ur; Ijaz, Ali Ahmad; Nasim, Humera (Journal of Rawalpindi Medical College, 2023)
Summary: Guillain-Barre Syndrome is an immune-mediated demyelinating disorder. Miller-Fisher Syndrome is an uncommon subtype of GBS. It is characterized by findings of ophthalmoplegia, ataxia, and areflexia. Here we present the case of Miller-Fisher Syndrome following an episode of typhoidal diarrhea. The presentation was of rapidly progressing weakness beginning in the lower extremity with diplopia. Examination revealed diminished reflexes. CSF testing revealed albuminocytologic dissociation which was later supported by neurophysiological testing. The patient was treated with intravenous immunoglobulins (IVIG). We conclude that Miller-Fisher syndrome should be considered in the diagnostic workup of patients presenting with new sensorimotor deficits following diarrheal illnesses and/or COVID-19 mRNA vaccination. Early recognition is essential given the propensity of GBS to cause life-threatening respiratory failure and prompt IVIG administration is associated with a better prognosis. Keywords: Enteric Fever, Miller-Fisher Syndrome, COVID-19, Vaccination